Current and Emerging Therapy for Celiac Disease - Makharia, Govind K. (Frontiers in Medicine, 2014)
At present, strict and lifelong gluten-free diet is the only effective treatment for celiac disease. Even small amounts of gluten (50 mg/day) can be immunogenic; therefore all food and food items and drugs that contain gluten and its derivatives must be eliminated completely from the diet. While prescribing gluten-free diet is easy; the key to the success is the dietary counseling by a nutrition specialist and maintenance of adherence to GFD by the patient. In recent times, a number of targets to halt the process of immunological injury have been explored to find out alternative treatment for celiac disease. These targets include exploration of ancient wheat if they are less immunogenic, intra-luminal digestion of gluten using prolylendopeptidases, pretreatment of whole gluten with bacterial-derived peptidase before ingestion; prevention of passage of immunogenic peptides through the tight junctions such as zonulin antagonists, Blocking of HLA-DQ2 to prevent binding of immunogenic peptides, inhibition of transglutaminase 2, immune-modulation, and induction of tolerance to gluten using gluten tolerizing vaccines, use of gluten-sequestering polymers, use of anti-inflammatory drugs (glucocorticoids, budesonides) and anti-cytokines such as anti TNF-α, and anti-interleukin-15. While many of these targets are still in the pre-clinical phase, some of them including zonulin antagonist and endopeptidases have already reached phase II and phase III clinical trials. Furthermore, while these targets appear very exciting; they at best are likely to be used as adjunctive therapy rather than a complete replacement for gluten-free diet.